From communication to humanization of disabled person - Żółkowska, Teresa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The ongoing systemic transformations have intensified the need to update the reflection on (disabled) people, their abilities or even their destiny. The political transformation that took place in our country chanced the scope and forms of social life. Economic and socio-cultural changes led to the disappearance of disabled people. As a result, it is necessary to rebuild a humanistic programme based on embracing the human being, their abilities and capabilities. One of the most important methods of working on the condition and prospects of (disabled) people is undoubtedly communication, and dialogue within its scope.